Analysis of depression status and influencing factors in middle-aged and elderly patients with chronic diseases - Lin, Wenjie; Zhang, Danling; Wang, YiMin; Zhang, Li; Yang, Jianchuan (Frontiers in Psychology, 2024)
Objectives: To explore prevalence of depression and its influencing factors in middle-aged and elderly patients with chronic diseases Method: Data were extracted from the 2018 China Health and Retirement Tracking Survey (CHARLS) for 6704 middle-aged and elderly patients ≥45 years with chronic diseases. The influencing variables were selected based on LASSO-logistic regression model, and a nomogram was further drawn to visualize regression results.Results: Comorbidity between chronic diseases and depression symptoms were detected in 3058 individuals (45.6%). Female, rural, lower education, poor, insomnia, multiple chronic disease, and functional impairment were associated with a higher proportion of depression. Meanwhile, family interaction, intergenerational financial support, social activity intensity, and satisfaction with life can protect against depression.Depressive symptoms are common in Chinese older adults with chronic diseases. They need regular assessment and intervention, especially those with multiple diseases, female, rural, alone, impaired, poor sleep, or poor economy. These high-risk elders also need family, medical, and social support and care.